2002
DOI: 10.1359/jbmr.2002.17.6.1111
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Gene Causing Autosomal Dominant Osteopetrosis Type I to Chromosome 11q12-13

Abstract: The osteopetroses are a heterogeneous group of genetic conditions characterized by increased bone density due to impaired bone resorption by osteoclasts. Within the autosomal dominant form of osteopetrosis, the radiological type I (ADOI) is characterized by a generalized osteosclerosis, most pronounced at the cranial vault. The patients are often asymptomatic but some suffer from pain and hearing loss. ADOI is the only type of osteopetrosis not associated with an increased fracture rate. Linkage analysis in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 16 publications
0
51
0
2
Order By: Relevance
“…Autosomal recessive and inactivating mutations in LRP5 decrease bone density in mice and humans (32,33,56). In contrast, activating mutations in LRP5 cause autosomal dominant high bone mass traits (34,35,59). The effects of these mutations on Runx2 activity have not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Autosomal recessive and inactivating mutations in LRP5 decrease bone density in mice and humans (32,33,56). In contrast, activating mutations in LRP5 cause autosomal dominant high bone mass traits (34,35,59). The effects of these mutations on Runx2 activity have not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Two Danish families with HBM were instrumental in localizing the disease-causing gene by linkage analysis on chromosome 11q12-13 (106). Within the delineated region, two genes of interest were localized: TCIRG1 encoding for the a3 subunit of the proton pump V-ATPase and LRP5 encoding for the LDL receptorrelated protein 5.…”
Section: Identification Of the Role Of The Lrp5 Gene In Bonementioning
confidence: 99%
“…Histological and metabolic studies of the ADOI patients, demonstrated increased trabecular and cortical thickness and a decrease in both osteoclast number and size. [1][2][3][4][5][6][7] The mutation causing ADOI was localized to chromosome 11q12-13 8 and later shown to be caused by gainof-function mutations in the low-density lipoprotein receptor-related protein 5 (LRP5). 9 Several other mutations in LRP5 were shown to lead to various osteopetrosis-like phenotypes, such as the high bone mass phenotype in G171V patients 10,11 and endosteal hyperostosis in A242T mutations.…”
mentioning
confidence: 99%
“…10,20,21 However, the patients with a T253I mutation have lower numbers of abnormally looking osteoclasts in vivo, 2 and whether this osteoclast phenotype in the T253I patients with ADOI is due to endogenous or exogenous factors is not yet known. To investigate the differentiation and function of osteoclasts from the T253I patients, we have previously characterized clinically and genetically, [1][2][3][4][5][6][7]22,23 we isolated CD14ϩ monocytes and cultured them under conditions promoting osteoclast development. We found no differences between ADOI and control osteoclasts in vitro, strongly suggesting that the ADOI phenotype in patients with a T253I mutation is caused by reduced ability of osteoblasts to support osteoclast development.…”
mentioning
confidence: 99%